Unprecedented Talent Program for China’s Strategic Goals - Wan, Xiaofeng (International Higher Education, 2020)
The Chinese ministry of education has announced a major reform in which the nation’s annual college entrance exam, the gaokao, plays a fundamental role. Titled “Foundation Enhancement Plan,” it takes unprecedented steps and resources to select and cultivate talents to feed directly into China’s national strategic goals. Thirty-six top-tier institutions are in the pilot group. The toughest admission criteria are in place to select the qualified few who will undergo rigorous learning throughout college and beyond to ensure China’s future success.